Penerapan Metode AHP dan Topsis dalam Penentuan Penerima Bantuan Program Keluarga Harapan - Nurul Azura; Yessica Siagian; Rika Nofitri (J-Com (Journal of Computer), 2021)
Abstract: The Family Hope Program (PKH) is a government program that provides cash to Very Poor Households (RTSM) based on the terms and conditions that have been established by carrying out their obligations. The purpose of the PKH is to reduce the number and break the poverty chain, improve the quality of human resources, and change behaviors that are less supportive of improving the welfare of the poorest groups. Determination of PKH aid recipients in the Coal Regency Social Service so far there are still shortcomings including not on target because the data of poor people is not up to date and the determination of criteria that have not been referred to the criteria that have been determined. For that, a system is needed that can help the process of determining PKH assistance recipients using the AHP and TOPSIS methods easily, quickly and precisely. This research aims to build the application of the decision support system of recipients of Family Hope Program (PKH) assistance in DinSos Coal Regency using AHP and TOPSIS methods. The results of this study can provide the best value based on predetermined criteria. Based on calculations using the AHP and TOPSIS methods, the decision was obtained that Rahmadan with a value of 1 and Nurul Ha with a value of 0.48 that deserved to be recommended as a recipient of PKH assistance. Keyword: AHP; TOPSIS; Help; Family Hope Program            Abstrak: Program Keluarga Harapan (PKH) merupakan suatu program pemerintah yang memberikan uang tunai kepada Rumah Tangga Sangat Miskin (RTSM) berdasarkan persyaratan dan ketentuan yang telah ditetapkan dengan melaksanakan kewajibannya. Adapun tujuan dari PKH tersebut untuk mengurangi angka dan memutus rantai kemiskinan, meningkatkan kualitas SDM, serta mengubah perilaku yang kurang mendukung peningkatan kesejahteraan dari kelompok paling miskin. Penentuan penerima bantuan PKH pada Dinas Sosial Kabupaten Batu Bara selama ini masih terdapat kekurangan diantaranya yaitu tidak tepat sasaran yang disebabkan data warga miskin tidak up to date dan penentuan kriteria-kriteria yang belum mengacu pada kriteria yang telah ditentukan. Untuk itu diperlukan sistem yang dapat membantu proses penentuan penerima bantuan PKH menggunakan metode AHP dan TOPSIS dengan mudah, cepat dan tepat. Penelitian ini bertujuan untuk membangun aplikasi sistem pendukung keputusan penerima bantuan Program Keluarga Harapan (PKH) pada DinSos Kabupaten Batu Bara menggunakan metode AHP dan TOPSIS. Hasil penelitian ini dapat memberikan perangkingan nilai terbaik berdasarkan kriteria yang telah ditentukan. Berdasarkan perhitungan dengan menggunakan metode AHP dan TOPSIS didapat keputusan bahwa Rahmadan dengan nilai 1 dan Nurul Ha dengan nilai 0.48 yang layak direkomendasi sebagai penerima bantuan PKH. Kata kunci: AHP; TOPSIS; Bantuan; Program Keluarga Harapan